Australian Retirement System: Significance of Pillars 3 and 4 in Achieving an Adequate Standard of Living in Retirement. Issue 3 (6th July 2019) - Evans, John R.; Razeed, Abdul
Abstract : Most research relating to the adequacy of the Australian retirement system has concentrated on Pillars 1 and 2. This paper indicates that there is a high probability that Pillars 3 and 4 will be needed to ensure an adequate standard of living in retirement, and in most scenarios, the contribution to retirement adequacy from Pillars 3 and 4 is very significant. We include an international comparison of equivalent Pillars 1 and 2 costs and conclude this analysis supports our results.